Antibacterial effect of bioactive glass incorporated in acrylic resins against Streptococcus mutans and Lactobacillus acidophilus activity in biofilm - Özer, Hazal; Özcan, Mutlu (Brazilian Dental Science, 2022)
Objective: The rough surfaces of removable appliances used in pediatric dentistry or orthodontics, may result in an environment for biofilm accumulation, yielding to enamel demineralization. This study aimed to assess the effects of adding nanoparticles of bioactive glass to polymethylmethacrylate to promote the antibacterial activity in acrylic resins. Material and Methods: Acrylic resin specimens (20x20x1mm3) were prepared by adding 2% or 5% bioactive glass. The specimens in the control group without bioactive glass were prepared from the mixture of acrylic powder containing nanoparticles and liquid monomer (n=10 per group). The antibacterial activity of the specimens against Streptococcus mutans and Lactobacillus acidophilus activity in biofilm was investigated through counting colony forming units (CFU). Data were analyzed using a one-way analysis of variance and Tukey’s post hoc tests at the significance level of 0.05. Results: The incorporation of 2% (p=0.001) and 5% (p<0.001) bioactive glass in acrylic resin reduced the metabolic activity and CFU of L. acidophilus. For S.mutans, antimicrobial activity was observed only with the 5% concentration of bioactive glass, and this group was statistically different from the control (p<0.001). When L. acidophilus was exposed to polymethyl methacrylate with 5% bioactive glass, significant decrease was observed compared to the control group (p<0.05). Conclusion: Adding bioactive glass nanoparticles into the acrylic resins used for fabricating removable appliances revealed a greater antibacterial effect against cariogenic bacteria tested. KEYWORDS Acrylic resins; Anti-bacterial agents; Bioactive glass; Dental materials; Pediatric dentistry.